THE ADMINISTRATIVE SKILLS OF ADMINISTRATORS AFFECTING ACADEMIC ADMINISTRATION OF SCHOOLS UNDER SAMUT PRAKAN PRIMARY EDUCATIONAL SERVICE AREA OFFICE 2 - Booupatumkul, Sasimaporn; Noymanee, Niwat; Saneechai, Atsavin (Journal of Education and Innovation, 2024)
The purpose of this research were: 1) to study the administrative skills of administrators under Samut Prakan Primary Educational Service Area Office 2, 2) to study relationship between the administrative and academic administration and 3) study to administrative skills of administrators affecting academic administration. Using stratified random sampling and tables of Krejcie and Morgan, to select 291 teachers under Samut Prakan Primary Educational Service Area Office 2. The research tool was a questionnaire, which validity (IOC) was between .80 - 1.00, reliability was at .91. The data were analyzed by frequency, percentage, mean, standard deviation, Pearson’s product moment correlation coefficients and multiple regression analysis by stepwise analysis. The research result were as follow: 1. The administrative skills of administrators was overall high ( = 4.32, SD = .75) 2. The correlations of administrative skills of administrators and academic administration was between .937 – .872 (significant level .01) and multi collinearity tolerance between .18 - .42, VIF between 4.25 - 6.24. 3. The administrative skills of administrators could predict academic administration was at .889. (significant level .05). The predictive power was at 88.90 percent, and were 2 variables, political skills (X5) and diagnostic skills (X4) regression with raw and standard scores as follows: Y = .796 +. 528 (X5) + .174 (X4) + .082 (X1) + .076 (X3) + (-.024) (X2) Z = .599 (X5) + .204 (X4) + .096 (X1) + .088 (X3) + (-.030) (X2)